2007
DOI: 10.1002/14651858.cd002181.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction for diabetic renal disease

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 64 publications
(37 reference statements)
4
98
1
5
Order By: Relevance
“…An increasing body of evidence suggests that dietary pattern intake rather than a sole focus on individual nutrients may offer a more practical approach to dietary management of chronic diseases (122-124). (126)(127)(128)(129)(130)(131)(132)(133).Theeffectsofalow-protein (daily intake of 0.6 g protein/kg ideal body weight), low-phosphorus (500-1,000 mg/day) diet were compared with those of a control diet containing $1.0 g protein/kg ideal body weight per day and $1,000 mg phosphorus per day in 35 patients with type 1 diabetes and DKD. Study participants on the lowprotein, low-phosphorus diet had a slower rate of decline in iothalamate GFR over the course of the study.…”
Section: Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…An increasing body of evidence suggests that dietary pattern intake rather than a sole focus on individual nutrients may offer a more practical approach to dietary management of chronic diseases (122-124). (126)(127)(128)(129)(130)(131)(132)(133).Theeffectsofalow-protein (daily intake of 0.6 g protein/kg ideal body weight), low-phosphorus (500-1,000 mg/day) diet were compared with those of a control diet containing $1.0 g protein/kg ideal body weight per day and $1,000 mg phosphorus per day in 35 patients with type 1 diabetes and DKD. Study participants on the lowprotein, low-phosphorus diet had a slower rate of decline in iothalamate GFR over the course of the study.…”
Section: Sodium-glucose Cotransporter 2 Inhibitorsmentioning
confidence: 99%
“…30 A subsequent meta-analysis, however, failed to demonstrate any significant effect of a low protein diet on GFR decline in 585 type 1 and type 2 diabetic patients included in 12 controlled studies. 31 On the other hand, evidence that glomerular capillary hypertension is often maintained by angiotensin-dependent mechanisms fueled a series of experimental studies aimed to test the long-term renoprotective effects of inhibitors of the RAS such as ACE inhibitors and ARBs. 32 At comparable systemic BP control, ACE inhibitors more effectively than combined therapy with hydralazine, reserpine, and a diuretic reduced glomerular capillary pressure and slowed disease progression in experimental models of CKD characterized by glomerular capillary hypertension such as reduced nephron mass 33 and streptozotocin-induced diabetes, 34 an effect that, again, was invariably associated with a consistent reduction in proteinuria.…”
Section: Therapeutic Advantages Of Ras Inhibitorsmentioning
confidence: 99%
“…Regarding diet therapy, the efficacy of a low-protein diet (LPD) for advanced diabetic nephropathy remains controversial [2]. Previous clinical studies have not consistently shown beneficial effects of an LPD for the preservation of renal function in diabetic nephropathy [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%